Step-by-step explanation:
You would solve it by turning it into a equation and solving it. You would place the dots on the graph and put them in the points where they are supposed to go.
The graph of f(x) = 0.5sin(4x) is sketched below
<h3>Graph of trigonometric functions </h3>
From the question, we are to sketch the graph of the given trigonometric function.
The given trigonometric function is
f(x) = 0.5sin(4x)
The graph of f(x) = 0.5sin(4x) is sketched below
Learn more on Graph of trigonometric functions here: brainly.com/question/4987799
#SPJ1
Answer:
![x=17](https://tex.z-dn.net/?f=x%3D17)
Step-by-step explanation:
![2x+3y=1](https://tex.z-dn.net/?f=2x%2B3y%3D1)
![y=-2-9](https://tex.z-dn.net/?f=y%3D-2-9)
- In order to combine these two equations, an idea you need to keep in mind is finding a way of setting these equations as equal to each other. I saw that each equation shared a common value,
. In this case, we need to isolate
in the first equation so that both equations
.
![2x+3y=1](https://tex.z-dn.net/?f=2x%2B3y%3D1)
![\frac{3y}{3}=\frac{-2x+1}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B3y%7D%7B3%7D%3D%5Cfrac%7B-2x%2B1%7D%7B3%7D)
![y=-\frac{2}{3}x+\frac{1}{3}](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B2%7D%7B3%7Dx%2B%5Cfrac%7B1%7D%7B3%7D)
- With this, we now know that both
and
are equal to
, so we can set them equal to each other.
![y=-\frac{2}{3}x+\frac{1}{3}](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B2%7D%7B3%7Dx%2B%5Cfrac%7B1%7D%7B3%7D)
![y=-11](https://tex.z-dn.net/?f=y%3D-11)
![-\frac{2}{3}x+\frac{1}{3}=-11](https://tex.z-dn.net/?f=-%5Cfrac%7B2%7D%7B3%7Dx%2B%5Cfrac%7B1%7D%7B3%7D%3D-11)
- Reply to this if anything I'm saying or doing is confusing in any way, or if you find a mistake. :) Solve for
.
![-\frac{2}{3}x+\frac{1}{3}=-11](https://tex.z-dn.net/?f=-%5Cfrac%7B2%7D%7B3%7Dx%2B%5Cfrac%7B1%7D%7B3%7D%3D-11)
![-\frac{2}{3}x=-11-\frac{1}{3}](https://tex.z-dn.net/?f=-%5Cfrac%7B2%7D%7B3%7Dx%3D-11-%5Cfrac%7B1%7D%7B3%7D)
![-\frac{2}{3}x =-\frac{33}{3}-\frac{1}{3}](https://tex.z-dn.net/?f=-%5Cfrac%7B2%7D%7B3%7Dx%20%3D-%5Cfrac%7B33%7D%7B3%7D-%5Cfrac%7B1%7D%7B3%7D)
![-\frac{2}{3}x =-\frac{34}{3}](https://tex.z-dn.net/?f=-%5Cfrac%7B2%7D%7B3%7Dx%20%3D-%5Cfrac%7B34%7D%7B3%7D)
![-\frac{2}{3}x(-\frac{3}{2})=-\frac{34}{3}(-\frac{3}{2})](https://tex.z-dn.net/?f=-%5Cfrac%7B2%7D%7B3%7Dx%28-%5Cfrac%7B3%7D%7B2%7D%29%3D-%5Cfrac%7B34%7D%7B3%7D%28-%5Cfrac%7B3%7D%7B2%7D%29)
![x=\frac{102}{6}=17](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B102%7D%7B6%7D%3D17)
![x=17](https://tex.z-dn.net/?f=x%3D17)
- Hopefully this answer is correct AND makes sense in terms of how I achieved it. Again, reply to this with any questions or mistakes I made and I'll do my best to answer or fix them.